Symposium 5: Perspectives on Institutional Implementation of e Learning: Stories and Ideas from a European Collaboration: Symposium Introduction - Deepwell, Frances (Proceedings of the International Conference on Networked Learning, 2004)
The symposium aims to explore different dimensions of implementing e-learning as revealed through narrative accounts from a diverse range of sources within 7 European universities. All papers are connected through the authors’ collaboration in the EQUEL project, E-quality in E-learning funded by the EU Commssion E-learning initiative. The EQUEL project has established a special interest group with an interest in the implementation of e-learning from an institutional perspective. The special interest group comprises researchers and developers from the Institut de Pédagogie universitaire et des Multimédias, University of Louvain Belgium; Laboratoire de Soutien à l’Enseignement Télématique, University of Liège, Belgium; Virtual Campus, E.M-Lyon, France; Centre for Higher Education Development, Coventry University, UK; Centre for Academic Practice, University of Warwick, UK; New Technologies for Education Centre, Fribourg University, Switzerland, Institutionen för pedagogik och didaktik, University of Goteborg, Sweden. Each one of these institutions has engaged in e-learning implementation with a unique rationale, overall strategy and set of technological and pedagogical tools at its disposal. The collaborative activity of the research group has uncovered and built new shared understandings about the factors influencing e-learning developments within and across our individual cultural domains.